Internet connectivity disruption in Oman (Oman) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Oman. Data sourced from IODA.
Network Disruption Incident ID: OM-2026-0059. Severity: critical. Confidence: 70%